Prevalence of Diabetes Mellitus, Impaired Fasting Glucose, and Impaired Glucose Tolerance in Thalassemia Major in Tabriz - Najafipour, Dr. Farzad (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Aim: Thalassemia major is an inherited blood disorder, and multiple blood transfusions are critical for survival in these patients. Over the last two or three decades, transfusion therapy in these patients has led to a significant improvement in life expectancy and quality of life. Iron overload is an uncommon complication of transfusion that occurs in patients after long periods. Endocrine abnormalities, which were not common in the past, are now among the most common complications in these patients. This study aimed to assess the prevalence of diabetes and glucose tolerance test in patients with thalassemia major, with 10–27 years of age in Tabriz. Methods: This descriptive study was performed on 56 patients between 10 and 27 years of age with thalassemia major in Tabriz. The demographic information, therapeutic regiment, the age of first transfusion, the level of blood transfusion, the history and dosage of familial history of diabetes, Fe, total iron-binding capacity, and ferritin levels were assessed and recorded. For each patient, fasting blood sugar and oral glucose tolerance tests were performed to diagnose of impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and diabetes. Results: According to the results, the prevalence of diabetes mellitus (DM), impaired fasting glucose, and impaired glucose tolerance test were found in 8.9%, 28.6%, and 7.1% of patients, respectively. Conclusion: This study showed that despite recent therapy with desferal in the management of beta-thalassemia major, the risk of secondary endocrine dysfunction remains high. Prevalence of DM, IFG, and IGT is greater than the general population. Endocrine evaluation in patients with thalassemia major must be carried out regularly, especially in those patients over the age of 10 years.